EVALUASI KINERJA OPERASIONAL BUS SEKOLAH KOTA DENPASAR - Servasius M. Said; Ida Bagus Made Parsa (Pranatacara Bhumandala: Jurnal Riset Planologi, 2020)
Denpasar city is known as a tourism and education city as a City worthy of children. Its high population density in Denpasar City Along with the variety of existing activities causes the occurrence of problems. To reduce congestion and minimize private vehicle use by students, the Denpasar city government provides free school buses for its students. This study aims to evaluate the Operational Performance of Denpasar School Buses by using the Descriptive Analysis method and Operational Performance Analysis and Quality of School Bus Service and SWOT Method to know the performance and strategy. The results showed that the operational performance is good enough with the Load factor value of 6 buses, the cost of bus ride 1-5 level of information reaches 70% but there is one bus that is bus 6 which the level of his condition is below 70%. The average journey-the distance is categorized as effective because it is under 40 km/h and travel time 40-60 minutes. The 2 and time departing and departing school with passenger waiting time below minus 5 minutes, student's walking distance to the drop zone below 400 meters. Based on the perception of school bus users in Denpasar that convenience, security, and implementation are the most important factors. Based on the SWOT results, the development strategy is in room A that is Rapid Growth, strategy, growth, and opportunities and increase potential.